Uncertainty Reduction Method Based on Statistics and Parallel Evolutionary Algorithms - Bianchini, Germán (2011)
In many scientific areas, the use of models to represent physical systems has become a common strategy. These models receive some input parameters representing some particular conditions and they provide an output representing the evolution of the system. Usually, these models are integrated into simulation tools that can be executed on a computational system. A particular case where models are very useful is the prediction of Forest Fire propagation. Therefore, the use of models is very relevant to estimate fire risk and to predict fire behaviour. However, in many cases the models present a series of limitations. Such restrictions are due to the need for a large number of input parameters and, usually, such parameters present some uncertainty due to the impossibility of measuring all of them in real time. In consequence, they have to be estimated from indirect measurements. To overcome this drawback and improve the quality of the prediction, in this work we propose a method that combines Statistical Analysis and Parallel Evolutionary Algorithms.